Grouping Students by Skill Level in Mini-Volleyball: Effect on Game Performance and Knowledge in Sport Education. Issue 4 (August 2021) - Mahedero, M. Pilar; Calderón, Antonio; Hastie, Peter; Arias-Estero, José L.
The purpose of this study was to explore any differences in game performance variables and knowledge among a cohort of high school students who participated in either homogeneous or heterogeneous skill level groups (N = 126) across a 12-lesson mini-volleyball sport education unit of study. This study followed a mixed-methods approach using a quasi-experimental pre-test/post-test design. The quantitative variables analyzed were decision making, skill execution, game performance, game involvement, and game knowledge. We also evaluated students' performance qualitatively, employing two methods: (a) experts' analysis of students' game performance, and (b) students' and teachers' perceptions of students' performance. We analyzed quantitative data through a series of paired samples t-tests comparing pre- and post-test scores according to the grouping strategy. Students became more competent in their game play and more knowledgeable in their technique, the sport's rules, tactical awareness, and general game knowledge. However, grouping students by skill level had no impact on gains in game performance variables and knowledge. Although sport education literature shows a preference for heterogeneity in ability-based grouping, within our data both heterogeneous and homogenous groups of higher and lower skilled students achieved improvements in game performance and knowledge, leading us to suggest that teachers who are interested in grouping students to create a meaningful learning experience should consider criteria other than student ability.